2007
DOI: 10.1111/j.1442-9071.2007.01535.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoexfoliation syndrome: in vivo confocal microscopy analysis

Abstract: Pseudoexfoliation (PEX) syndrome is a common ocular disease that also affects the cornea. A case of clinical PEX syndrome, studied by in vivo corneal confocal microscopy is reported. The morphological analysis of the confocal images demonstrated hyper-reflective deposits and several dendritic cells in the basal epithelial layer. A fibrillar subepithelial structure was also found. The endothelial layer showed cell anomalies (polymegathism and pleomorphism) and hyper-reflective small endothelial deposits. Confoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 5 publications
0
21
2
3
Order By: Relevance
“…This special endotheliopathy can cause early corneal endothelial decompensation and may have been previously misdiagnosed as an atypical non-guttata Fuchs' endothelial dystrophy (8,18,19) . In addition, in vivo confocal microscopy studies have shown significant morphologic alterations in the corneas of PXS patients (5,(20)(21)(22) . Data are indicated as mean ± standard deviation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This special endotheliopathy can cause early corneal endothelial decompensation and may have been previously misdiagnosed as an atypical non-guttata Fuchs' endothelial dystrophy (8,18,19) . In addition, in vivo confocal microscopy studies have shown significant morphologic alterations in the corneas of PXS patients (5,(20)(21)(22) . Data are indicated as mean ± standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue differentiation predisposes to several intraocular and surgical complications, including glaucoma, zonular dehiscence, phacodonesis and lens subluxation, capsular rupture or vitreous loss during cataract surgery, blood-aqueous barrier dysfunction, and corneal endothelial decompensation (3,4) . In previous studies, the deposition of exfoliation material on the corneal endothelium, decreased endothelial cell density, changes of the basal epithelium with the alterations of the subepithelial nerve plexus, decreased corneal sensation, and dry eye with the disturbances of the precorneal tear film have been reported (5)(6)(7)(8) . However, there are conflicting studies about central corneal thickness (CCT) in patients with PXS or pseudoexfoliative glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…И ни в одном из них не оценивались такие показатели, как распростра-нённость дендритических клеток и гиперрефлек-тивных межклеточных микровключений, выра-женность очагов десквамации поверхностного эпителия и уплотнения боуменовой мембраны. Martone et al указали на единичный случай на-личия дендритических клеток и гиперрефлектив-ных межклеточных микровключений при ПЭС [23]. Несколько авторов отметили возможность визуализации ПЭМ на эндотелии роговицы при помощи конфокальной микроскопии [12,24,25].…”
Section: Discussionunclassified
“…A few studies in the literature have used in vivo corneal confocal microscopy to study the corneas of patients with PEX. Martone et al detected hyperreflective deposits and den dritic cells infiltrating the basal epithelial cell layer in one case using in vivo corneal confocal microscopy (7) . They also found fibrillar subepithelial structures, and the endothelial layer showed cellular anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have described the changes in the histopathological endothelial characteristics (3,7,12) , although few used in vivo cor neal confocal microscopy to analyze the possible differences between patients with and without PEX. Zheng et al observed not only lower endothelial cell density but also increased degrees of pleomorphism and polymegathism and a higher coefficient of variation in the cell sizes in the patients with PEX compared with those in the healthy control subjects (3) .…”
Section: Discussionmentioning
confidence: 99%